2019
DOI: 10.1155/2019/3618103
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in CDKAL1 Gene Are Associated with Risk of Gestational Diabetes Mellitus in Chinese Population

Abstract: Gestational diabetes mellitus (GDM) is a growing public health concern for many reasons, and its etiology remains unclear. Due to the similarity of its pathophysiology with type 2 diabetes (T2DM), we evaluated the relationship between published T2DM susceptibility genes and the risk of GDM. A total of 303 SNPs from genes including IRS1, IGF2BP2, CDKAL1, GCK, TCF7L2, KCNQ1, and KCNJ11 and the risk of GDM were examined in a nested case-control study with 321 GDM cases and 316 controls. The odds ratios (ORs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…The rs7747752 under study was significantly associated with increased GDM risk. Similar to our findings, another study also found that Chinese women with the rs7747752 polymorphism were predisposed to a high risk of GDM ( 8 ). Previous studies have reported significant interaction effects of CDKAL1 with lifestyle interventions, SFAs, and vitamin D on GDM risk ( 14 , 17 , 33 ).…”
Section: Discussionsupporting
confidence: 91%
“…The rs7747752 under study was significantly associated with increased GDM risk. Similar to our findings, another study also found that Chinese women with the rs7747752 polymorphism were predisposed to a high risk of GDM ( 8 ). Previous studies have reported significant interaction effects of CDKAL1 with lifestyle interventions, SFAs, and vitamin D on GDM risk ( 14 , 17 , 33 ).…”
Section: Discussionsupporting
confidence: 91%
“…Thus far, most genetic investigations of GDM have highlighted variants that are already known to increase risk of T2D (40,41), underscoring the overlap in the genetic architecture of the two conditions. Most studies have investigated known T2D-associated loci using GDM case-control studies in populations of various ethnic backgrounds including European, African American, Chinese, and Hispanic (42)(43)(44)(45)(46). The T2D-associated loci that have been most robustly associated with GDM are IRS1, IGF2BP2, CDKAL1, GCK, TCF7L2, MTNR1B, KCNJ11, and KCNQ1 (40).…”
Section: Known T2d-associated Loci and Gdmmentioning
confidence: 99%
“…There is a strong association between common T2D risk gene polymorphisms and GDM [ 79 ]. Five of the most identified genes in GDM are: (1) Transcription factor 7-like 2 [TCFL7L2] [ 80 , 81 ]; (2) Melatonin receptor 1B [MTNR1B] [ 82 , 83 ]; (3) CDK5 regulatory subunit-associated protein 1-like 1 [CDKAL1] [ 84 , 85 ]; (4) Potassium voltage-gated channel, KQT-like subfamily, member 1 [KCNQ1] [ 86 , 87 ]; and (5) Insulin receptor substrate-1 [IRS1] [ 88 , 89 ]. The most recent and comprehensive searches in the genetic and epigenetic etiology of GDM have been reviewed elsewhere [ 90 , 91 ].…”
Section: Risk Factors For Gdmmentioning
confidence: 99%